2008
DOI: 10.1017/s0033291707002516
|View full text |Cite
|
Sign up to set email alerts
|

Debt, income and mental disorder in the general population

Abstract: BackgroundThe association between poor mental health and poverty is well known but its mechanism is not fully understood. This study tests the hypothesis that the association between low income and mental disorder is mediated by debt and its attendant financial hardship.MethodThe study is a cross-sectional nationally representative survey of private households in England, Scotland and Wales, which assessed 8580 participants aged 16–74 years living in general households. Psychosis, neurosis, alcohol abuse and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
210
2
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(237 citation statements)
references
References 24 publications
15
210
2
10
Order By: Relevance
“…Debt also appears to be more common in suicide completers , (Chan et al, 2009;Chen et al, 2006;Wong et al, 2008;, and increases the risk of suicidal ideation and attempts after controlling for possible confounds such as mental illness (Hintikka et al, 1998;Meltzer et al, 2011). Individual studies have shown a relationship with drug use, problem drinking and drug dependence as well as tobacco smoking (Berg et al, 2010;Jenkins et al, 2008;Meltzer et al, 2013;Nelson et al, 2008;Roberts et al, 1999;2000;Stuhldreher et al, 2007;Webley & Nyhus, 2001). In terms of mental health, many studies have shown a relationship with common mental disorders (Clark et al, 2012;Cooper et al, 2008;Meltzer et al, 2013;Patel et al, 1998;Pothen et al, 2003), and global mental health as measured by the General Health Questionnaire (Goldberg, 1991Brown et al, 2005Finlay-Jones & Eckhardt, 1984;Gathergood, 2012;Hatcher, 1994;Hintikka et al, 1998;Roberts et al, 1999;2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Debt also appears to be more common in suicide completers , (Chan et al, 2009;Chen et al, 2006;Wong et al, 2008;, and increases the risk of suicidal ideation and attempts after controlling for possible confounds such as mental illness (Hintikka et al, 1998;Meltzer et al, 2011). Individual studies have shown a relationship with drug use, problem drinking and drug dependence as well as tobacco smoking (Berg et al, 2010;Jenkins et al, 2008;Meltzer et al, 2013;Nelson et al, 2008;Roberts et al, 1999;2000;Stuhldreher et al, 2007;Webley & Nyhus, 2001). In terms of mental health, many studies have shown a relationship with common mental disorders (Clark et al, 2012;Cooper et al, 2008;Meltzer et al, 2013;Patel et al, 1998;Pothen et al, 2003), and global mental health as measured by the General Health Questionnaire (Goldberg, 1991Brown et al, 2005Finlay-Jones & Eckhardt, 1984;Gathergood, 2012;Hatcher, 1994;Hintikka et al, 1998;Roberts et al, 1999;2000).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly debt is defined differently. For example for the analysis on problem drinking, Jenkins, et al (2008) defined debt as being currently behind on a tax or bill, whereas Stuhldreher, et al (2007) look at those who have been in debt due to gambling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor (mental) health is often associated with less engaged parenting and a reduced ability to emotionally attend and respond to children's needs; these, in turn, can affect the psychological and emotional well-being of children. In addition, it should be underlined that the economic resources and mental health of parents are not independent of each other: economically disadvantaged individuals are more likely than advantaged ones to experience psychological problems (for example, see Readings and Reynolds, 2001); but, in turn, socio-economic deprivation and financial difficulties frequently coincide with mental health difficulties (Hudson, 2005;Jenkins et al, 2008). On the other hand, the literature documents that both the material resources and the parents' health vary considerably across living arrangements.…”
Section: Why Does Family Structure Matter For Adolescents' Well-being?mentioning
confidence: 99%
“…Factors like household indebtedness, unemployment and impoverishment are potentiated in times of economic crisis and play a crucial role in the development of mental illnesses (Jenkins et al 2008;Reading and Reynolds 2001;Skapinakis et al 2006;Taylor et al 2007; WHO 2011) predisposing people to a higher risk of mental health problems such as major depression, alcohol consumption and suicide (Dee 2001;Dooley et al 1994;Dorling 2009;Lewis and Sloggett 1998;Mathers and Schofield 1998;McKee-Ryan et al 2005;Murphy and Athanasou 1999).…”
Section: Introductionmentioning
confidence: 99%